1989
DOI: 10.1055/s-2007-1024928
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Long-Distance Running on Iron Metabolism and Hematological Parameters

Abstract: In 110 well-trained participants of a 1000-km running competition lasting for 20 days hematological parameters, iron metabolism, and their respective changes during the race were investigated. Thirty-nine men and 11 women were accustomed to wholesome vegetarian food (lacto-ovovegetarian), 52 men and 8 women consumed a conventional western diet. In each group 50% of the runners finished the race. Before the competition started red blood cell count, hematocrit, and hemoglobin were on average below the values obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
3

Year Published

1994
1994
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 7 publications
2
26
0
3
Order By: Relevance
“…Similarly, higher (21-76%) excretion of magnesium 28 and zinc 29,30 was found in trained athletes compared to controls. Moreover, several investigators have found iron in urine 23,31 or faeces 23,[32][33][34][35] after strenuous endurance running. However, it is likely that iron excretion is much less during moderate training.…”
Section: Factors Potentially Affecting Micronutrient Requirements In mentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, higher (21-76%) excretion of magnesium 28 and zinc 29,30 was found in trained athletes compared to controls. Moreover, several investigators have found iron in urine 23,31 or faeces 23,[32][33][34][35] after strenuous endurance running. However, it is likely that iron excretion is much less during moderate training.…”
Section: Factors Potentially Affecting Micronutrient Requirements In mentioning
confidence: 99%
“…However, sodium losses, particularly, may be significant [11][12][13][14][15][16][17] (Table 1). The losses of magnesium [11][12][13][14]17 , iron 11,[18][19][20][21][22][23] and zinc 11,21 through sweat may also be meaningful, compared with the daily needs for body, after intestinal absorption is accounted for 24,25 . However, the interpretation of the data is difficult, because of several problems in sweat analyses.…”
Section: Factors Potentially Affecting Micronutrient Requirements In mentioning
confidence: 99%
“…A very low variability (8.2%) was reported by Belza et al [2] for iron-depleted women. Physical exercise may considerably increase ferritin levels as reported for cross-country skiers [21] or female triathletes [23] and those exercise-induced increases may persist for several days [12,27], which may affect the day-to-day variability. Similar observations were made by us in male and female judoists in whom the within-subject, day-to-day variability averaged 27.4 and 46%, respectively, highest individual values amounting to 44 and 75%, respectively [14,16].…”
Section: ±1mentioning
confidence: 99%
“…However, detecting that deficiency in physically active individuals is difficult due to possible exercise-induced changes in iron metabolism indices, especially ferritin. Increased ferritin levels were reported immediately post-exercise [21,23] and even several days following strenuous exertions [12,27]. In most studies on the effects of exercise on iron metabolism, its indices were determined before…”
Section: Introductionmentioning
confidence: 99%
“…Nutrient intake, haemoglobin level and endurance time were better in non-vegetarians than lacto, ovolacto vegetarians 20 . Vegetarian athletes had low energy intake with low levels of vitamins and minerals 21 such as B-complex, calcium, iron, and zinc 22,23 . Since majority of the selected participants of the present study were non vegetarians, they are less likely to develop any vitamin and mineral deficiency.…”
Section: Dietary Patternmentioning
confidence: 99%